The Relationship Between Workplace Learning and Sustainable Leadership of Perak Secondary School Teachers: Hubungan Antara Pembelajaran Tempat Kerja Dengan Kepimpinan Lestari Guru Sekolah Menengah Negeri Perak - Mansor, Mahaliza; Mat Jizat, Jessnor Elmy; Ishak, Rosnah; Ponimin, Nor Farhana (Management Research Journal, 2021)
The main purpose of this study was to identify the relationship of workplace learning with teacher sustainable leadership. In addition, this study also examines the level of formal learning practices, informal learning, and incedental learning and the level of sustainable leadership practices among teachers. This quantitative study involved a total of 375 samples from 40 secondary schools in the state of Perak which were selected by using stratified random sampling and systematic random sampling. The Cronbach’s Alpha value for the workplace learning items was .934, meanwhile for sustainable leadership was .955. Data were analyzed using descriptive and inferential statistics. Overall, the findings of the teacher workplace learning level were at a moderate level with the mean value 3.64, SD = 0.517. In addition, the level of teacher sustainable leadership was at a high level with mean value 4.03, SD = 0.425. There was a significant positive relationship between workplace learning with teacher sustainable leadership with a value of r = 0.648 (p